Optimisation of biogas generation from brown seaweed residues: Compositional and geographical parameters affecting the viability of a biorefinery concept. (15th October 2018) - Tedesco, S.; Daniels, S.
Highlights: Biorefined seaweed residues demonstrated high potential for producing biogas. Ambient extractions cascade improved the CH4 and biodegradation potentials. Average CH4 yields on an annual basis were found between 107 and 405 mL gVS −1 . Seasonal composition and harvest site greatly affect digestion performance. Abstract: Very recently, integrated biorefinery approaches are being developed with the aim to produce high-value products for a variety of industries in conjunction with green energy from sustainable biomass. Macroalgae (seaweed) have been regarded as more sustainable compared to terrestrial crops, since they do not occupy land for growth. Macroalgal biomass changes greatly according to species and harvest season, which affects its chemical energy potential. This study was conducted seasonally on five species of brown seaweed over a yearlong period to investigate the effects of chemical composition variations, bioproducts extraction processes and inoculum acclimatation on methane production. As a result of the bioproducts extraction, it was found the seaweed residues exhibit a great potential to produce methane. Stoichiometric methane yield and C:N ratio changed in favour of an improved digestibility with bioconversion rates greater than 70% in some instances, i.e. achieved by Laminaria species and on the West coast Fucus serratus . The two Laminaria species investigated also presented the highest CH4 production rate, with Laminaria digitata reaching 523 mL CH4 gVS −1 and L . saccharina peaking at 535 mL CH4 gVS −1 with acclimatised and non-acclimatised sludge respectively.